2009
DOI: 10.1016/j.brainres.2009.02.082
|View full text |Cite
|
Sign up to set email alerts
|

ERP correlates of the incidental retrieval of emotional information: Effects of study-test delay

Abstract: Prior studies indicate that, in tests of recognition memory, ERPs elicited by correctly recognized test items differ according to whether the items were encoded in an emotionally arousing or an emotionally neutral study context. These prior studies employed only a relatively brief (ca. 10 min) retention interval, however. The present study contrasted the ERP correlates of incidental emotional retrieval as a function of study-test delay. Pictures of emotionally neutral objects were encoded in association with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
44
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 23 publications
12
44
1
2
Order By: Relevance
“…In accordance with this suggestion, in behavioral research it has been observed that recognition of emotional contextual cues compared to neutral ones is enhanced after long (such as 1 or 7 days), but not after short delays (Pierce & Kensinger, 2011;. Recently, two ERP studies have investigated emotional contextual binding (Jaeger et al, 2009;Jaeger & Rugg, 2012) on a delayed test (24 hours). However, Jaeger and colleagues found no better memory for neutral objects encoded in emotionally unpleasant background scenes compared to those neutral objects associated with neutral scenes, indicating that beneficial effects of contexts may occur after longer consolidation periods (c.f., Pierce & Kensinger, 2011).…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…In accordance with this suggestion, in behavioral research it has been observed that recognition of emotional contextual cues compared to neutral ones is enhanced after long (such as 1 or 7 days), but not after short delays (Pierce & Kensinger, 2011;. Recently, two ERP studies have investigated emotional contextual binding (Jaeger et al, 2009;Jaeger & Rugg, 2012) on a delayed test (24 hours). However, Jaeger and colleagues found no better memory for neutral objects encoded in emotionally unpleasant background scenes compared to those neutral objects associated with neutral scenes, indicating that beneficial effects of contexts may occur after longer consolidation periods (c.f., Pierce & Kensinger, 2011).…”
mentioning
confidence: 76%
“…computer monitor located 150 cm in front of the participant. In contrast to previous studies (e.g., Jaeger et al, 2009;Jaeger & Rugg, 2012;Smith, Dolan, et al, 2004, Smith, Henson, Dolan, & Rugg, 2004Smith, Henson, Rugg, & Dolan, 2005), in which objects were visually separated (white background and/or yellow frame), here objects were presented with transparent background and without frame to facilitate object-scene binding. Objects were presented in one of four quadrants of the screen.…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations